1992
DOI: 10.1088/0954-3899/18/11/014
|View full text |Cite
|
Sign up to set email alerts
|

Some general properties of projectile fragments in40Ar interactions in nuclear emulsions at 1.8 A GeV

Abstract: An analysis of projectile fragments has been performed using 40Ar-emulsion interactions at 1.8A GeV. The interaction mean free path of "'Ar nuclei was obtained on the basis of 46W events which enabled us to calculate the total inelastic cross section. Correlations between the multiplicity of different charged particles were studied extensively to get an insight into the reaction mechanism. The average number of interacting nucleons of the projectile was calculated and compared with results from other experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…The projectile helium fragments with charge Z ¼ 2, have been studied earlier in nuclear emulsion experiments from the point of view of limiting fragmentation by Heckman et al 22) and by Bhanja et al 5) at 2.1 A GeV energy. In this sequence, some other authors [23][24][25] further confirmed this hypothesis experimentally for projectile helium fragments in nucleus-nucleus interactions in later years. Such a quantitative study of limiting fragmentation hypothesis on the experimental basis for the projectile helium fragments in nucleus-nucleus interactions at 14.6 A GeV has not been performed so far.…”
Section: Introductionsupporting
confidence: 75%
“…The projectile helium fragments with charge Z ¼ 2, have been studied earlier in nuclear emulsion experiments from the point of view of limiting fragmentation by Heckman et al 22) and by Bhanja et al 5) at 2.1 A GeV energy. In this sequence, some other authors [23][24][25] further confirmed this hypothesis experimentally for projectile helium fragments in nucleus-nucleus interactions in later years. Such a quantitative study of limiting fragmentation hypothesis on the experimental basis for the projectile helium fragments in nucleus-nucleus interactions at 14.6 A GeV has not been performed so far.…”
Section: Introductionsupporting
confidence: 75%
“…( 5), <N  > = a (A T ) b . (5) Where, A T represents the average target mass number of different target groups based on the number of heavily ionizing charge particle N h in 84 Kr -Emulsion interactions. The best fitting parameters are a = 0.20±0.06 and b = 0.37±0.04 for 84 Kr -Emulsion interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The various concepts of nuclear physics are extrapolated with heavy-ion collisions and it is essential to check their application in wide range of incident energies i.e. 1 to 200 GeV/n [5][6]. According to the participant spectator model (PS Model) [7][8][9], the interacting systems are divided into three different regions: projectile spectator (PS), target spectator (TS) and participant region i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the frame of the Becquerel Collaboration [1] nuclear emulsion was exposed to beams of light nuclei of 1-3.7 A GeV and the results obtained from the investigation of nuclear diffraction dissociation are given in [2][3][4][5][6][7]. Valuable results were obtained by other authors, for 16 O, 24 Mg and 28 Si at 3.7 A GeV [8], for 16 O at 14.6, 60 and 200 A GeV [9], as well as for 16 O and 28 Si at 200 A GeV [10,11].…”
Section: Methodsmentioning
confidence: 99%